1962
DOI: 10.1152/jappl.1962.17.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Sweating and body temperatures following abrupt changes in environmental temperature

Abstract: Human subjects were transferred between environments imposing different levels of heat stress. Analyses of measurements obtained after a reasonably steady state had been achieved in each of several environments revealed equally good correlation between a) sweat rate and ear temperature (tympanic membrane), and b) sweat rate and calculated deep skin temperature (hypothetical). The correlations are consistent with adjustment of sweating in response to either hypothalamic temperature or temperature of skin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Studies by Belding and Hertig (1962);McCook et'al. (1965);Stolwijk and Hardy (1966a, b) and those in our own laboratory (Bullard, 196~;Van Beaumont and Bullard, 1965) have been in a range consistent enough to discourage investigators from attributing a sweating drive to skin temperature per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Belding and Hertig (1962);McCook et'al. (1965);Stolwijk and Hardy (1966a, b) and those in our own laboratory (Bullard, 196~;Van Beaumont and Bullard, 1965) have been in a range consistent enough to discourage investigators from attributing a sweating drive to skin temperature per se.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of the effect of the neural impulses.Such a mechanism has also been reported by Lloyd (1961) using the foot pad of the cat and direct neural stimulation. Benjamin (1953) working with small areas of human skin has concluded that local heating facilitates the central effects on the Sweat gland. Ina control system model this action would be represented as a multiplier rather than a summer in its interaction with the neural impulses arriving at the gland.…”
Section: Discussionmentioning
confidence: 99%
“…5) and more recently Belding and Hertig (ref. 4) have observed steady state sweating values during both rest and exercise to fall on a common line when plotted against tympanic membrane temperature. The intersection of this line with the temperature baseline represents the set point for sweating which would thus be the same for both rest and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In man evaporative loss from the lung isusually regarded as minor and Unregulated in comparison with dermal evaporative loss (Belding and Hertig, 1962;Gagge, 1964;Hardyi 1961;Thauer, 1961). Yet in some warm-blooded vertebrates pulmonary evaporative loss is a main avenue of heat control.…”
Section: Discussionmentioning
confidence: 99%